(untitled) (Estudios Humanísticos. Filología, 1996)
Literary texts that were not central have acquired relevance and this phenomenon has been already approached and studied in profusion. A case of exceptional acceptability is that of some topics bom around the most representative romantic poets. "Frankenstein" has been rewritten by Brian Aldiss, Frankenstein Unbound which was also transformed into a SF I will study in which terms the dialogue of B. Aldiss with his own literary and historical past was established, and his textual debt, his own interpretation and adaptation of the myth and his role as an artist in this transformation